Clinical Indications Of Suvarna Malini Vasantha – An Experiencial And Scientific View - Shripathi, Acharya G; Acharya, Rajeshwari S (International Research Journal of Ayurveda & Yoga, 2020)
Swarna Malini Vasantha is a herbomineral rasashastriya formulation which is commonly prescribed in day to day practice. Especially chronic disorders like chronic fever, rickets, chronic non healing ulcer , mental retardation in children, ADHD, delayed mile stone development in children etc. It contains Swarna bhasma, shuddha hingula, Naga bhasma, Vanga bhasma, shuddha kharpara and pippali choorna and swetamaricha These ingredients are nadi balya, mastishka balavardhaka, rasayana and dhatwagni vardhaka in action.The present paper highlights about the clinical indications of swarna Malini Vasantha in a Experiential and scientific view.